The effects of Nigella sativa extract on hypothyroidism-associated learning and memory impairment during neonatal and juvenile growth in rats. (2nd January 2017) - Beheshti, Farimah; Hosseini, Mahmoud; Shafei, Mohammad Naser; Soukhtanloo, Mohammad; Ghasemi, Simagol; Vafaee, Farzaneh; Zarepoor, Leila
Abstract : Objectives : It has been shown that hypothyroidism-induced oxidative damage in brain tissue is involved in its adverse effects on learning and memory. Nigella sativa ( N. sativa ) has been suggested to have antioxidant and neuroprotective effects. The objective of this study was to investigate the effects of hydroalcoholic extract of N. sativa on hypothyroidism-associated learning and memory impairment during neonatal and juvenile growth in rats. Methods : Thirty pregnant rats were kept in separate cages. After delivery, the mothers and their offspring were randomly divided into six groups including: (1) control, (2) PTU (propylthiouracil), (3) PTU-NS 100, (4) PTU-NS 200, (5) PTU-NS 400, and (6) PTU-Vit C (vitamin C). All dams except the control group received 0.005% PTU in their drinking water during lactation. Besides PTU, dams in groups 3, 4, 5, and 6 received 100, 200, and 400 mg/kg N. sativa extract, or 100 mg/kg Vit C, respectively. After lactation period, pups continued to receive same experimental treatment for the first 8 weeks of their life. Then, 10 male offspring of each group were randomly selected and assessed for the learning and memory abilities by using Morris water maze (MWM) and passive avoidance (PA) tests. Blood samples were collected for thyroxine assessment, animals were euthanized, and the brain tissues were removed and analyzed for total thiol groups and malondialdehyde (MDA) concentrations. Results : PTU exposure significantly increased the time latency in MWM test, while reduced the time spent in target quadrant, and decreased the latency for entering the dark compartment in PA test. These effects were associated with significant reduction in serum thyroxine levels and brain levels of thiol groups, and significant elevation in hippocampal MDA. Administration of 400 mg/kg N. sativa extract and 100 mg/kg Vit C reduced the time latency, while increased the time spent in target quadrant compared to the PTU group in MWM test. Treatment by 100–400 mg/kg of N. sativa extract and also Vit C significantly increased the time latency for entering the dark compartment in PA test. The serum thyroxine concentrations of the animals treated by all doses of the N. sativa extract as well as by Vit C were higher than that of the PTU group. Two hundred and four hundred milligrams/kilogram of NS extract and 100 mg/kg Vit C decreased the MDA concentration in hippocampal tissues, while increased thiol contents compared to the PTU group. Discussion : The results of this study demonstrate that the hydroalcoholic extract of N. sativa have protective effects on hypothyroidism-associated learning and memory impairment during neonatal and juvenile growth in rats. The effects were comparable to Vit C and might be due to the protective effects of N. sativa extract against brain tissues' oxidative damage.